Enantiopure Conducting Salts of Dimethylbis(ethylenedithio)tetrathiafulvalene (DM‐BEDT‐TTF) with the Hexachlororhenate(IV) Anion (Eur. J. Inorg. Chem. 24/2014). Issue 24 (August 2014) - Pop, Flavia; Allain, Magali; Auban‐Senzier, Pascale; Martínez‐Lillo, José; Lloret, Francesc; Julve, Miguel; Canadell, Enric; Avarvari, Narcis
Abstract : The cover picture shows the mirror‐image relationship, like that between the two hands in the background, between two enantiopure dimethylbis(ethylenedithio)tetrathiafulvalene (DM‐BEDT‐TTF) precursors. Also shown are the solid‐state packing diagrams, represented in an artistic manner, of the mixed‐valence radical cation salts of these precursors with the hexachlororhenate(IV) dianion. These paramagnetic semiconducting chiral materials have been obtained by electrocrystallization, and their transport properties were determined by single‐crystal resistivity measurements, supported by band‐structure calculations. The organic/inorganic segregation shown in the picture is an important prerequisite for extensive electron delocalization, although charge localization occurs here in the donors. Details are discussed in the article by N. Avarvari et al. onp. 3855 ff . For more on the story behind the cover research, see theCover Profile .